2021
DOI: 10.1039/d0na01014f
|View full text |Cite
|
Sign up to set email alerts
|

Giant photoluminescence enhancement in MoSe2 monolayers treated with oleic acid ligands

Abstract: The inherently low photoluminescence (PL) yields in as prepared transition metal dichalcogenide (TMD) monolayers are broadly accepted to be the result of atomic vacancies (i.e. defects) and uncontrolled doping, which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…This bulky form of tungsten also slows down the reaction enabling a better control of the reactivity. In addition, it has been recently demonstrated that the addition of long ligands has a beneficial effect on the trap passivation, which leads to a photoluminescence enhancement in the case of the 2H phase. , This observation suggests that long ligands can be incorporated within the TMDC crystalline structure. For this synthesis, we use a combination of long-chain amines and thiols (acting as solvent as well), and we slowly inject into the hot reaction mixture the tungsten and chalcogen precursors. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This bulky form of tungsten also slows down the reaction enabling a better control of the reactivity. In addition, it has been recently demonstrated that the addition of long ligands has a beneficial effect on the trap passivation, which leads to a photoluminescence enhancement in the case of the 2H phase. , This observation suggests that long ligands can be incorporated within the TMDC crystalline structure. For this synthesis, we use a combination of long-chain amines and thiols (acting as solvent as well), and we slowly inject into the hot reaction mixture the tungsten and chalcogen precursors. …”
Section: Resultsmentioning
confidence: 99%
“…The latter can be controlled through the right choice of ligands . In the previous reference, carboxylic acids have been used to prevent aggregation during growth, but they introduced at the same time oxide defects in the structure. , To avoid this issue, here, we are instead using thiols as stabilizing ligands. In a large excess, they also complex the tungsten precursor to form thiolates.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a second smaller peak is present at ~90 nm below (i.e. at ~200 meV higher energy), which corresponds to the B-exciton (higher spin-orbit split state) [56]. The ratio of the intensities of the A and B peak emissions is usually connected to the defect density in the samples [57].…”
Section: Photoluminescence Propertiesmentioning
confidence: 99%
“…31 In terms of applying for selenium-based compounds, oleic acid treatments on MoSe 2 succeeded in enhancing PL intensity. 26 In addition, hydrohalic acid treatment on MoSe 2 showed PL enhancement. 27 Defect repairing in the crystalline lattice has been suggested for the enhancement of PL intensity in the case of MoSe 2 .…”
mentioning
confidence: 97%
“…2,[6][7][8][9][10][11][12][13][14][15] However, a drawback of the optical behavior in monolayer TMDCs is their poor optical property, such as poor photoluminescence (PL) intensity, causing factors such as over-carrier concentrations, [16][17][18][19] strains, [20][21][22] and defects in the crystalline lattice. [23][24][25][26][27] In the case of the n-type materials of MoS 2 and WS 2 , p-type doping successfully enhances PL intensity with chemicals such as p-dopants of 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ) 19,28 and tetrafluoro-1,4benzoquinone 29 . The p-dopant enhances exciton (electron-hole pair) dominant emission by decreasing the probability of generating trion (two electrons and hole pair) in TMDCs.…”
mentioning
confidence: 99%